Carbon Nanotubes: Carbon Nanotubes for Photovoltaics: From Lab to Industry (Adv. Energy Mater. 3/2021). Issue 3 (20th January 2021) - Wieland, Laura; Li, Han; Rust, Christian; Chen, Jianhui; Flavel, Benjamin S.
Abstract : In article number 2002880 Jianhui Chen, Benjamin S. Flavel and co‐workers discuss the breakthroughs in growth, processing and separation of carbon nanotubes that have enabled their use in new forms of organic and silicon‐based photovoltaics. Recent and rapid advancements in the efficiency and area of these solar cells suggest that carbon nanotube photovoltaics will soon leave the laboratory setting and enter commercial production lines.